Public Institution Fights on Financial Management during Pandemic Crisis - Mateen Tashfeen; Zaryan Shahmeer (Journal La Bisecoman, 2020)
This study discusses about the financial management, investation decision,which is include about the funding decision, and devided decision. The finanncial management porpuse to maximize profit or profit and minimize costs in order to obtain a maximum decision making in running the company towards the development and running company. Managing finances during the pandemic namely (1) adjust variable expenses using the average method (2) prioritize mandatory and necessary (3) pay off high-interest consumer debt, and don’t add more (4) keep an emergency fund where it sholud be (5) thinking twice about making a profit from insurance (6) still set aside money for investment (7) just set aside 10% of income for things that are desire.